Formation of a Nomenclature of Indicators of Household Appliances Quali-ty and Its Qualification Assessment - Olga KOTOMENKOVA; Anna VINOGRADOVA (Communications of International Proceedings, 2020)
The article proposes an algorithm for the formation of a nomenclature of quality indicators and qualification assessment of household appliances. The range of quality indicators is formed on the basis of the applicability of products to a group, taking into account the definition of complex quality indicators and single quality indicators of different levels. Qualification assessment was carried out by an expert method based on the calculation of a comprehensive quality indicator taking into account the weighting coefficients of individual indicators of quality and safety of individual consumer properties of technical products.
Keywords: Household Appliances; Quality of Household Devices and Machines; Nomenclature of Quality Indicators; Qualification Assessment.